H.C. Taylor papers - Taylor, H. C. (Henry Clay), 1845-1904.
Correspondence, diary, writings, printed matter, photographs, and other papers relating chiefly to the Spanish-American War and to Taylor's command of the USS Indiana (Battleship : BB-1). Taylor's writings include an unpublished novel, "Naroonya." Correspondents include George Dewey, Samuel C. Lemley, Stephen Bleecker Luce, C.R.P. Rodgers, and William Thomas Sampson.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Division and at
Forms part of: Naval Historical Foundation collection.
Naval officer.
Keywords: Dewey, George, -- 1837-1917 -- Correspondence; Luce, Stephen Bleecker, -- 1827-1917 -- Correspondence; Lemley, Samuel C. -- Correspondence; Rodgers, C. R. P. -- 1819-1892 -- Correspondence; Sampson, William Thomas, -- 1840-1902 -- Correspondence; United States. -- Navy -- History -- Spanish-American War, 1898.; Indiana (Battleship : BB-1); Spanish-American War, 1898 -- Naval operations; Naval officers